Foreign experience in protecting state sovereignty and territorial integrity and potentials of its application in Ukraine - Berezhnoi, S. M.; Бережной, С. М. (Підприємництво, господарство і право. - 2022. - № 10. - С. 18-24, 2022)
Узагальнено досвід захисту державного суверенітету та територіальної цілісності провідних країн Європи, зокрема Великобританії, Німеччини та Франції. Відзначено, що суттєвий вплив на розвиток законодавства цих країн має те, що вони є членами Європейського Союзу та Організації Об’єднаних Націй. Запропоновано власне бачення щодо можливих напрямів імплементації найбільш позитивного зарубіжного досвіду захисту державного суверенітету та територіальної цілісності у вітчизняних реаліях.

The purpose of the article is to analyse the foreign experience in protecting State sovereignty and territorial integrity and feasibility of its application in Ukraine. Results. The author proves the need for scientific research on the foreign experience in protecting State sovereignty and territorial integrity. It is noted that each State has formulated its own special approach to protecting State sovereignty and territorial integrity due to: first, the specifics of historical and legal development of each individual State; second, its social, economic and political development; and third, the geographical location of the State. The author summarises the experience in protecting the State sovereignty and territorial integrity of the leading European countries, in particular, Great Britain, Germany and France. The author argues that these countries’ membership in the European Union and the United Nations has a significant impact on the development of their legislation. The author offers his own vision of possible trends in implementing the most positive foreign experience in protecting State sovereignty and territorial integrity in the national realities. Conclusions. To sum up, the following foreign experience in protecting State sovereignty and territorial integrity in the Ukrainian state is most appropriate: 1) Ukraine should bring its domestic legislation in line with the requirements of the European Union in the field of protection of State sovereignty and territorial integrity as soon as possible, as the experience of a number of European countries shows that their legislation is based on the principles of sovereignty enshrined in the EU's regulatory sources; 2) The Ukrainian legislator should review the organisational structure of the system of entities whose activities are aimed at protecting the State sovereignty and territorial integrity of Ukraine; 3) It is advisable to create an effective mechanism of interaction between the relevant actors; 4) It is necessary to adopt the experience of states in terms of full financial and logistical support of the relevant agencies; 5) It is essential to develop an effective Strategy for the protection of State sovereignty and territorial integrity, which has been effectively implemented in leading countries, for example, the UK.

Обобщен опыт защиты государственного суверенитета и территориальной целостности ведущих стран Европы, в частности, Великобритании, Германии и Франции. Отмечено, что существенное влияние на развитие законодательства этих стран оказывает то, что они являются членами Европейского Союза и Организации Объединенных Наций. Предложено собственное видение возможных направлений имплементации наиболее позитивного зарубежного опыта защиты государственного суверенитета и территориальной целостности в отечественных реалиях.
Зарубіжний досвід захисту державного суверенітету й територіальної цілісності та можливості його використання в Україні
Keywords: державний суверенітет; територіальна цілісність; захист; адміністративно-правове регулювання; зарубіжний досвід; адміністративне законодавство; state sovereignty; territorial integrity; protection; administrative and regulatory framework; foreign experience; administrative legislation; государственный суверенитет; территориальная целостность; защита; административно-правовое регулирование; зарубежный опыт; административное законодательство